The Evaluation of body dysmorphic disorder in adult orthodontic patients - Fatemeh Masoumi; Mahdiye Asghari; Sajjad Shirkhouii (Cumhuriyet University, 2022)
Introduction: The present study aimed to evaluate body dysmorphic disorder (BDD) in orthodontic patients. Also, the relation between demographic factors and BDD was investigated. Materials and Methods: This descriptive-analytical cross-sectional study was performed on 320 patients referred to the dental clinic. Participants were excluded if they had craniofacial syndromes, visible physical inabilities, mental diseases such as depression and OCD, and required orthognathic surgery. The YBOCS-BDD was used to assess BDD. Fisher's exact test was performed using SPSS Version 24 at the significance level of P=0.05. Results: 47.5% of patients were normal and 34.4% had mild BDD and 17.2% had moderate BDD, and only 0.9% of the patients had severe BDD. A significant relation was found between gender and BDD, and between marital status and BDD. (P=0.004 and P<0.001, respectively). The relation of age and severity of BDD was not statistically significant. Conclusion: BDD disorder in orthodontic patients is more common in women and single people. In this regard, it is recommended that cosmetic clinicians be careful in accepting patients with a history of mental and personality problems, multiple and frequent esthetic surgeries, and if necessary, persuade and refer the patient to a psychiatrist and counselor to prevent the consequences.